Exposure to a Specific Pulsed Low-Frequency Magnetic Field: A Double-Blind Placebo-Controlled Study of Effects on Pain Ratings in Rheumatoid Arthritis and Fibromyalgia Patients - Naomi M Shupak; Julia C McKay; Warren R Nielson; Gary B Rollman; Frank S Prato; Alex W Thomas (Pain Research and Management)
BACKGROUND: Specific pulsed electromagnetic fields (PEMFs) have been shown to induce analgesia (antinociception) in snails, rodents and healthy human volunteers.